Pedagogika twórczości w tradycji europejskiej. Ujęcie retrospektywne = Pedagogy of creativity in European tradition. Retrospective approach - Bartkowiak, Edyta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The essence of creative education and schools consists in creating opportunities and situations in the child`s environment that foster the release of the child?s potential and in enabling the child to develop spontaneously through activity and independent effort. The basis of creative education is the recognition and inclusion of the child?s innate abilities and interests, whereas the basis of the work in creative schools is the rule of experiencing and cooperating.
Keywords: edukacja twórcza; szkoła twórcza; wychowanie twórcze; creative education; creative school; raising a creative child